Higher rate of severe toxicities in obese patients receiving dose-dense (dd) chemotherapy according to unadjusted body surface area: results of the prospectively randomized GAIN study - Furlanetto, Jenny; Eiermann, Wolfgang; Marmé, Frederik; Reimer, Toralf; Reinisch, Mattea; Schmatloch, Sabine; Stickeler, Elmar; Thomssen, C.; Untch, Michael; Denkert, Carsten; Minckwitz, Gunter von; Lederer, B.; et al. (Annals of oncology, 2016)
BackgroundIn routine clinical practice, chemotherapy doses are frequently capped at a body surface area (BSA) of 2.0 m2 or adjusted to an ideal weight for obese patients due to safety reasons.Materials and methodsBetween August 2004 and July 2008, a total of 3023 patients were enrolled in the GAIN study, a randomized phase III adjuvant trial, comparing two types of dose-dense (dd) regimen [epirubicin, docetaxel and cyclophosphamide (iddETC) versus epirubicin and cyclophosphamide (EC) followed by docetaxel (T) plus capecitabine (X)]. We retrospectively evaluated a total of 555 patients with a BMI of ≥30 for safety and outcome.ResultsEighteen percent of all patients were obese: 31% of those received chemotherapy according to an unadjusted BSA. For the remaining patients, BSA was adjusted to ideal weight or was capped at 2.0 m2. A total of 15% of obese patients receiving full (unadjusted) dose of chemotherapy versus 6% of obese patients with an adjusted BSA experienced febrile neutropenia (P = 0.003) and 9% versus 3% high-grade thrombopenia (P = 0.002). Overall, 17% versus 10% had a thromboembolic event (P = 0.017), which was high grade in 13% versus 6%, respectively (P = 0.019), and 3% versus 0.3% high-grade hot flushes (P = 0.013). Dizziness (5% versus 11%; P = 0.016), diarrhea (19% versus 27%; P = 0.033) and an increase in serum creatinine (7% versus 14%; P = 0.019) were higher in the adjusted group. However, no differences in disease-free survival (DFS) and overall survival (OS) were observed between non-obese patients, obese patients receiving full-dose chemotherapy or according to an adjusted BSA [5-year DFS 81% (confidence interval 79% to 83%) versus 82% (75% to 87%) versus 81% (76% to 84%); P = 0.761; 5-year OS 90% (88% to 91%) versus 86% (80% to 91%) versus 88% (84% to 91%); P = 0.143].ConclusionObese patients receiving dd chemotherapy according to their real BSA have a higher risk of developing severe toxicities without influencing survival. Therefore, a dose adjustment of intense dd chemotherapy should be carried out to avoid life-threatening complications.